2019
DOI: 10.1097/md.0000000000016464
|View full text |Cite
|
Sign up to set email alerts
|

Increased renal cortical stiffness is associated with coronary artery disease severity in patients with acute coronary syndrome

Abstract: Atherosclerosis is the primary etiological factor associated with acute coronary syndrome (ACS). Kidneys have a highly arterial vascular structure and are therefore commonly affected by atherosclerosis, including those affecting the coronary arteries. Renal shear wave elastography (SWE) is an ultrasonographic method, which provides reliable information regarding the condition of the renal parenchyma. We investigated the relationship between SWE findings and the severity of coronary atherosclerosis. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 20 publications
(26 reference statements)
0
1
0
Order By: Relevance
“…However, our results came in contrast with Demirtaş and Bulut who reported that RRI in the low-risk ACS patients (mean SYNTAX Score 12) was 0.73 0.07 while in high risk patients (mean SYNTAX Score 12) was 0.76 0.08 without significant differences between both groups. Higher RRI observed in this high risk group may be related to acute stress, however, non-significant difference could be attributed to difficult Doppler assessment of the kidneys due to retroperitoneal location, difficult assessment in obese patients and limited efficacy of shear wave elastography (SWE) using the acoustic radiation force impulse imaging modality in the kidneys located deeper than 5 cm [ 37 ]. Of note, these results could be considered as novel ones as the study exclusively included stable CAD patients; not ACS patients, without renal impairment (eGFR 50 mL/min/1.73 ).…”
Section: Discussionmentioning
confidence: 99%
“…However, our results came in contrast with Demirtaş and Bulut who reported that RRI in the low-risk ACS patients (mean SYNTAX Score 12) was 0.73 0.07 while in high risk patients (mean SYNTAX Score 12) was 0.76 0.08 without significant differences between both groups. Higher RRI observed in this high risk group may be related to acute stress, however, non-significant difference could be attributed to difficult Doppler assessment of the kidneys due to retroperitoneal location, difficult assessment in obese patients and limited efficacy of shear wave elastography (SWE) using the acoustic radiation force impulse imaging modality in the kidneys located deeper than 5 cm [ 37 ]. Of note, these results could be considered as novel ones as the study exclusively included stable CAD patients; not ACS patients, without renal impairment (eGFR 50 mL/min/1.73 ).…”
Section: Discussionmentioning
confidence: 99%